2018
DOI: 10.1111/tct.12764
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional learning in ambulatory care

Abstract: Ninety-two students undertook the interprofessional placement: 74% were medical students and 26% were nursing students. The overall response rate was 81%. Students strongly supported the model of clinical supervision with the nurse educator and teaching registrar working collaboratively to facilitate the placement. Both medical and nursing students felt that the placement facilitated the development of interprofessional principles, with 78.7% agreeing or strongly agreeing with the statement 'the clinical place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…48 The medical students' existing stereotypes about nursing students were challenged because they found that the nursing students had wider competencies than expected; this experience altered their attitude toward nursing students in general, as described in the literature. 24,25,39 Furthermore, by observing the nursing students' focus on the patients' activities in daily life, the medical students broadened their picture of the patient, from examining only X-rays and range of motion to having a more holistic view about what is important for patients in their daily life, e.g., how much weight the patient was allowed to carry when going shopping.…”
Section: Interprofessionalmentioning
confidence: 99%
See 1 more Smart Citation
“…48 The medical students' existing stereotypes about nursing students were challenged because they found that the nursing students had wider competencies than expected; this experience altered their attitude toward nursing students in general, as described in the literature. 24,25,39 Furthermore, by observing the nursing students' focus on the patients' activities in daily life, the medical students broadened their picture of the patient, from examining only X-rays and range of motion to having a more holistic view about what is important for patients in their daily life, e.g., how much weight the patient was allowed to carry when going shopping.…”
Section: Interprofessionalmentioning
confidence: 99%
“…21,22 Similar positive results have been reported from interprofessional clinical learning in outpatient clinics. [23][24][25] To our knowledge, a comparison of uniprofessional dyadic training versus interprofessional dyadic training of medical students in an authentic setup in a busy outpatient clinic has not been described. Based on the current literature, dyadic training seems to have the potential for peer learning in both situations.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include engagement in shared educational curricula, modules or short courses, e.g., [ 6 , 7 , 8 ], or shared conference events, e.g., [ 9 ]. Alternatively, it may involve face-to-face interactive opportunities; these are most often focused within clinical environments and may entail collaborative working during student placements in clinical settings [ 10 , 11 ], assessment of clinical skills in a team situation [ 12 ]: Team Objective Structured Clinical Examination; OSCE), engagement in clinical simulated experiences [ 13 , 14 , 15 ], or consideration of clinically-focused case studies or scenarios [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…9]. Alternatively, it may involve face-to-face interactive opportunities; these are most often focused within clinical environments and may entail collaborative working during student placements in clinical settings [10][11], assessment of clinical skills in a team situation [12]: Team Objective Structured Clinical Examination; OSCE), engagement in clinical simulated experiences [13][14][15], or consideration of clinically-focused case studies or scenarios [16][17][18].…”
Section: Introductionmentioning
confidence: 99%